Stakeholder Perspectives on Access and Benefit-Sharing for Areas Beyond National Jurisdiction - Collins, Jane Eva; Vanagt, Thomas; Huys, Isabelle (Frontiers in Marine Science, 2020)
Negotiations for a new international legally binding instrument under the United Nations Convention on the Law of the Sea for the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction (ABNJ) are currently ongoing. A ‘package’ of four elements are under discussion, one of which is ‘marine genetic resources (MGR), including questions on the sharing of benefits’. Governance of MGR in ABNJ requires consideration of access and benefit-sharing options. The MGR element is considered the most contentious since there is a lack of convergence on this topic amongst delegates. This is currently hindering progress in negotiations. Therefore, resolving issues linked to MGR holds the key to reaching agreement of the instrument as a whole. The aim of this paper is to gather stakeholder perspectives on goals and options for a new genetic resource mechanism for ABNJ. A scoping literature review was conducted to identify goals and options in terms of access and of benefit-sharing in ABNJ. Next, semi-structured interviews were conducted with 24 people from five different stakeholder groups; scientific research community, private sector, developing States, developed States and civil society. Results indicated that stakeholders all agree with conservation and sustainable use of marine biological diversity of ABNJ as the most important goals of a potential new genetic resource mechanism for ABNJ. Stakeholders preferred a light-touch governance approach to access, with notification pre- (and possibly also post-) collection of MGR in situ. Mandatory non-monetary benefit-sharing at point of sampling was considered most appropriate, possibly with scope for voluntary monetary benefit-sharing at the point of commercialisation. It may be useful to keep these perspectives in mind during negotiations and also during future implementation processes in order to attain the goals of perceived greatest importance. By understanding the different view-points and priorities, delegates will be better equipped to negotiate the remainder of the issues related to MGR, to reach mutually-acceptable compromises and, ultimately, a new BBNJ agreement.